GAMBARAN LINGKUNGAN, KEPUASAN KERJA DAN LOYALITAS KARYAWAN EL ROYALE HOTEL BANDUNG - Rahayu, Meida Aditya; Senen, Syamsul Hadi; Razati, Girang (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this study is to see the description of work environment, job satsfaction, and employee loyalty. Design/methodology/approachh - The design of this study was cross sectional method. This research uses descriptive approach with explanatory survey method. A total of 110 respondents were selected using probability sampling. A questionnaire was used as a research instrument to collect data from respondents. Analytical technique used is descriptive technique by using frequency distribution.Findings - Based on the results of the research using descriptive analysis, the results obtained that the work environment is in the quite good category with a score 68,83, job satisfaction and employee loyalty are in the quite high category with a score of respectively 70,57% and 71,68%.Originality/value -Â  This study provides a basis for understanding issues of work environment, job satisfaction, and employee loyalty. The difference of this study with the previous research is located on the object which is the company in the service industry that is El Royale Hotel Bandung, with the variables studied namely work environment, job satisfaction, and employee loyalty, and using different theory or reference from previous researcher.